PENGARUH PENDIDIKAN-PELATIHAN (DIKLAT) DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA APARATUR SIPIL NEGARA DENGAN MEDIASI KOMPETENSI PADA DINAS KOPERASI, PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN SITUBONDO - Adhadi, Rifki; Karnadi, Karnadi; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2022)
The human resources needed today are human resources who have the knowledge, abilities, skills and good attitudes at work. The purpose of this study was to analyze and examine the effect of education-training (Training) and Organizational citizenship behavior on the performance of ASN with competence mediation. This research is an explanatory research. The population in this study is the state civil apparatus of the Department of Cooperatives, Industry and Trade, Situbondo Regency. The sampling technique used was saturated sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Education-training (Training) has a significant effect on Competence, Organizational Citizenship Behavior has a significant effect on Competence, Education-training (Training) has a significant effect on ASN Performance, Organizational Citizenship Behavior has no proven effect significant effect on ASN Performance, Competence has a significant effect on ASN Performance. The results of the indirect effect hypothesis test show that the variable Education-training (Training) on ​​ASN Performance through Competence has a significant positive effect, Organizational citizenship behavior on ASN Performance through Competence has a significant positive effect.